Power in Africa: a comparison of selected South African and Nigerian dystopian fiction - Simelane, Smangaliso (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2020)
Dystopias have frequently been explored in literature to better understand the present and imagine the effects of certain elements of society if taken to a logical extreme. In this way, dystopian fiction can act as both cautionary tales and a form of social commentary. This can be explored within the context of African dystopian fiction where power is a recurring theme, highlighting the anxiety and turbulent history several countries on the continent continue to face. To demonstrate this, I compare selected South African and Nigerian Dystopian texts. With regards to South Africa, I analyse novels by South African science fiction authors Lauren Beukes and Lily Herne, namely Moxyland (2008) and Deadlands (2011) respectively, to investigate how South Africa's past under Apartheid shapes the segregated societies presented. Nigerian dystopian texts by Biyi Bandele-Thomas, namely The Sympathetic Undertaker And Other Dreams (1993) and The Man Who Came in from the Back of Beyond (1992), are discussed with regards to the way Nigeria's colonial past and several military juntas have contributed to the kinds of corruption that are depicted. I argue that all four texts warn of the dangers of power, albeit in ways that pertain specifically to their countries of origin. With regards to the South African texts, readers are shown the ways in which those in power can manipulate the desire to survive to keep those they subjugate dependent and, consequently, obedient through what Judith Butler terms 'passionate attachments'. In the case of the Nigerian dystopias, I argue that Bandele-Thomas's texts warn of tyranny and effects of the corruption that result from misused power strategies. While the dire settings of dystopian fiction may be grim enough, on their own, to motivate change in the real world, this may not be enough to prevent the texts from becoming pessimistic and fatalistic outlooks. Hence, I seek to understand how the selected novels maintain hope and, consequently, convince readers that the depicted dystopias are ones that can be avoided. Typically, dystopian literature fosters hope by setting the narratives in the future, giving readers hope that they may take steps today to protect their societies from becoming like the damned worlds described by dystopian authors. However, the selected texts are not set in the future. Hence, I explore three literary techniques that might foster hope within the selected African dystopian texts in lieu of temporal distancing. They are, namely: identification with the protagonist, defamiliarization and cognitive estrangement.
Keywords: Dystopias in literature; Africa -- In literature; South African fiction (English) -- History and criticism; Nigerian fiction (English) -- History and criticism; Beukes, Lauren -- Moxyland; Herne, Lily -- Deadlands; Bandele-Thomas, Biyi, 1967- The Sympathetic Undertaker and Other Dreams; Bandele-Thomas, Biyi, 1967- The Man Who Came in from the Back of Beyond